2x-4(x-3)=-9+5x-7

Simple and best practice solution for 2x-4(x-3)=-9+5x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4(x-3)=-9+5x-7 equation:



2x-4(x-3)=-9+5x-7
We move all terms to the left:
2x-4(x-3)-(-9+5x-7)=0
We add all the numbers together, and all the variables
2x-4(x-3)-(5x-16)=0
We multiply parentheses
2x-4x-(5x-16)+12=0
We get rid of parentheses
2x-4x-5x+16+12=0
We add all the numbers together, and all the variables
-7x+28=0
We move all terms containing x to the left, all other terms to the right
-7x=-28
x=-28/-7
x=+4

See similar equations:

| q=1/2=1 | | (3x+1)+71=180 | | 5x+23=2x+10 | | X^2+8=2.5^x | | -2(x+3)5x=-39 | | 11=-2(3y-5) | | 2=6/g | | 10z=8z+8 | | h+2/2=3 | | -9-4x=59 | | -3(7a-6)=2-5a | | 3x-9=x=+1 | | 32x=2(8x-4) | | 1=x+3/22 | | -3(6-4)+a5=-26-2 | | 22+3n=3(n+5) | | -5(x+1)=-5x-11 | | -6-7x=-6(1+5x) | | 26/r=2 | | t²+2t-15=0 | | -8(1-7x)=-7x-8 | | 6(a+1)=a-29 | | s+1/4=4/ | | -2-7x=-6+3(x+8) | | 8+n/4=-9 | | 2(8-p)=14-3p | | 5(-2p-3)-1=6p | | 7/6y-12=-5 | | 12/4y-13=-1 | | 46x=53x | | 180(n-2)=168*n | | f(1+2)=3f(1+1)-2f(1) |

Equations solver categories